Loser becomes Winner: Translating Reality Shows for the Arab World - Almaiman, Nourah (2012)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Nourah Almaiman entitled, Loser Becomes Winner: Translating Reality Shows for the Arab World." Thesis advisor is Dr. Said Faiq and was submitted in April 2012. Available are both hard and soft copies of the thesis.